Elaboración de vermi compost con residuo de cosecha y producción de rábano (Raphanus sativus L). - Ortiz Freire, Milton Rodrigo (2015)
Study on the Experimental "La Playita" of the UTC Center located geographical WGS 84: latitude S0 ° 56' 27 "Length W 79 ° 13' 25"; It is taken as a general objective of study, determine the development of vermi compost with crop residues and production of radish (Raphanus sativus L). the specific, and improve agricultural production through the provision of organic fertilizer, measure the response of the organic fertilizer in the cultivation of horseradish, set the level of profitability of the production of organic fertilizer and the cultivation of horseradish, using a design completely at random (DCA) with four treatments and four replications. The results were: the production of humus in kilograms was 50,00 kg, production of humus in manure bobino 40% residual pastures 60% with 20.80 kg; conversion of production/humus manure bobino 40% Rasquis banana 20% vegetable residues 20% waste of pasture 20% with 2, 77.En production of radish manure bobino 40% Rasquis banana 20% vegetable residues 20% waste of pasture 20% by weight of the radish with 0.95 kg; and diameter of bulb in the same treatment with 3.62 cm. In soil analysis of the concentrations of nitrogen and phosphorus in EB 40% RB 60 2.30% and 0.37% on your order, potassium EB 40% 60% RB and EB 40% 60% RV indicated the same value with 1.04%; EB 40% 60% RV in calcium and magnesium with 1.98 and 0.53% respectively; sulfur all treatments 0.20%. In PPM boron indicated in EB 40% 60% RB and EB 40% 60% with 32 ppm RP; Zinc and iron with 103 and 933 ppm in its order on EB 40% RB 60%; Copper and manganese EB 40% 60% RV with 219 and 32 ppm. Economically the manure bobino 40% Rasquis banana 20% 20% vegetable residue residue of 20% pasture, is the treatment that gets higher cost of production on fertilizer with $2.13 per kg, as well as, the higher income in the production of radish with $ 209,00.